Determination of Groundwater Surface using Damped Least-Squares Inversion in the Bekasap Field, Riau - Pinehas, D; Warsa, Warsa (Jurnal Geofisika, 2019)
Groundwater is a primary water source for the sustainability of human life. Groundwater is located in the subsurface area in the saturated zone called aquifer. The presence of an aquifer can be identified through a geophysical survey by determining the upper boundary of the aquifer called the groundwater table. DC Resistivity geoelectrical method is one of the geophysical measurements which is effective to be used to determine the depth of the water table. Measurements were performed using the Wenner electrode configuration in Bekasap to attain preferable depth resolution. The process of measurement data modelling yields rms error. In order to reduce the rms error, damped least-squares is applied into the inversion solution. This process will improve the model parameter iteratively until the minimum rms error is obtained. The damped least-squares modeling was tested on three synthetic models which have Resistivity variation. Furthermore, the damped least-squares was applied on the observed data at Bekasap. From the processing and modeling using damped least-squares, the depth of the groundwater table and aquifer can be obtained.